Abdominal wall desmoid tumors: A proposal for US-guided resection. (2015) - Bolzon, Stefano; Vagliasindi, Alessio; Zanzi, Federico; Negri, Marco; Guerrini, Gian Piero; Rossi, Camilla; Soliani, Paolo
Highlights: We need to optimize tissue sparing for the best abdominal wall reconstruction. We need to obtain a oncological safe procedure. Using US technology to identify tumor edge. This kind of US guided surgery can improve abdominal wall surgical resection reducing tissue loss. Abstract: Background: Desmoid tumors (DTs) is a benign tumor with high tendency to infiltrative evolution and recurrence. Nowadays, in abdominal localization, the standard approach is surgery with R0 condition. The need to repair post-surgical wide wall defect requires conservative technique to decrease the incidence of incisional hernia and to obtain better quality of life (QoL). Methods: We perform an abdominal wall desmoid resection using ultrasound guide. This technique ensures to spare a wide wall area and to obtain a multilayer reconstruction minimizing postoperative risk. This approach allows good oncological results and better managing abdominal wall post-resection defect. Results: We use US guided surgery to get radical approach and wall tissue spare that allows us a multilayer reconstruction minimizing post-operative complications. No recurrences were observed in one year follow up period. Conclusion: Our experience represents first step to consider ultrasound mediated technique usefull to optimize wall resection surgery and to minimize following complications.